Importance of International Humanitarian Law (IHL) Training in Armed Police Force, Nepal - Bam, Narendra; Shrestha, Raju; Maharjan, Ram Krishna (Journal of APF Command and Staff College, 2020)
International humanitarian law (IHL) applies at times of armed conflict, placing legal obligations on all warring parties that are designed to limit the inhumanity of warfare. Armed Police Force (APF), Nepal with the mandate to control an armed struggle occurred or likely to occur in any part of Nepal, to control armed rebellion or separatist activities or likely to occur in any part of Nepal, and to provide assistance in case of external intervention being under the Nepali Army, can at any time become a party in both international and non-international armed conflict. APF’s role in UN Peacekeeping Missions is also an area where it may have to engage with non-state actors if and when situation demands. All these necessitate APF personnel to have proper understanding and compliance to the principles of IHL, violation of which can increase human suffering and consequent individual criminal responsibility and command responsibility. In light of this, it concludes the IHL specific trainings in APF, Nepal should be maintained and augmented to ensure broad and better understanding and respect for IHL in times of conflict.